Selection function in breakage processes: PBM and Monte Carlo modeling - Das, Ashok; Bück, Andreas; Kumar, Jitendra (Advanced Powder Technology, 2020)
Breakage, i.e., formation of smaller fragments from larger initial particles, is an important phenomenon – wanted or unwanted – in many particulate processes. In this work, the volume and time dependent selection function for pure breakage process is modeled based on the population balance modeling approach. It is found that the selection function is directly correlated with the stressing frequency, probability of successful events, and some integral properties of the number density function. A discrete population balance equation is applied to compute the total number of particles and particle size distribution numerically. Moreover, an event-driven constant number Monte Carlo simulation algorithm is presented, and the simulation results are used as an alternative to experimental results. The volume dependency of the selection function is incorporated successfully in the Monte Carlo simulation while selecting particles for stressing event. Some important properties of any particulate process, such as the total number of particles and the size distribution of particles are validated successfully using the Monte Carlo results. This offers new insights into the estimation and interpretation of breakage kinetics.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Breakage; Monte Carlo simulation; Population balance equation; Selection function; Stressing frequency